Loss of WNK1 Suppressed the Malignant Behaviors of Hepatocellular Carcinoma Cells by Promoting Autophagy and Activating AMPK Pathway - Wang, Fang; Yan, Xianxia; Shi, Guangyan; Zhang, Lei; Jing, Xu (Disease Markers, 2022)
Background. WNK lysine deficient protein kinase 1 (WNK1) has been shown to be highly expressed in hepatocellular carcinoma (HCC) samples and related to poor prognosis of HCC patients based on bioinformatics analysis. However, the specific function of WNK1 in HCC has not been analyzed. This study is aimed at exploring the function of WNK1 in HCC progression as well as its related molecular mechanism. Methods. After knockdown of WNK1 by small interference RNA, cell counting kit-8, colony formation, western blot, Transwell, and wound healing assays were employed to evaluate the biological behaviors of HCC cells. Immunofluorescent staining was applied to detect the effect of WNK1 on LC3 II. GSK690693 or si-AMPK was applied to block AMPK pathway. The expression of autophagy and AMPK pathway related molecules was examined by western blot assay. Results. WNK1 was highly expressed in HCC cell lines and loss of WNK1 inhibited HCC cell proliferation, cell cycle, migration, and invasion. Additionally, we demonstrated that loss of WNK1 promoted the autophagy and activated AMPK pathway in HCC cells. While, GSK690693 treatment or si-AMPK transfection suppressed the autophagy and promoted HCC cells proliferation. However, WNK1 knockdown counteracted the effect of GSK690693 or si-AMPK in regulating HCC cell proliferation. Finally, we demonstrated that WNK1 regulated the malignant behaviors of HCC cells by modulating autophagy and AMPK pathway. Conclusions. The above results indicated that WNK1 may be a worthwhile target to be considered for therapy of HCC.